Improving the productivity of crop-livestock systems under trypanosomosis risk in West Africa: Potentials and opportunities in the next decade - Kamuanga, M.; D'Ieteren, G.D.M.; Tano, K.; Mugalla, C.; Pokou, K.; Swallow, B.M. (International Livestock Research Institute, 2004)
The subhumid and semi-arid zones of West Africa are one of the subregions reputed to hold Africa's greatest potential for expansion of animal agriculture. Within this region livestock are affected by tsetse-transmitted trypanosomosis-a disease that severely constrains productivity, thus hampering efforts to meet the continent's future food security needs. Improved management of livestock diseases will directly facilitate increases in the amounts of milk and meat produced. Indirectly, this will lead to an increase in the value of crops and livestock produced, particularly through changes in the number of draft animals available for traction. Between 1994 and 1999, the International Livestock Research Institute (ILRI) in partnership with national research systems and regional institutions undertook socio-economic research at the farm, community and market levels at several sites in Burkina Faso, C6te d'Ivoire and The Gambia. This research has provided knowledge of the factors affecting adoption of animal disease control techniques and approaches to evaluate the impacts and sustainability of improved strategies and techniques for livestock production under varying trypanosomosis risk. A three-pronged approach was used to understand the constraints and assess opportunities for increasing the productivity of crop-livestock systems at selected sites. The paper presents a summary review of: 1. analysis of livestock practices and management approaches in different production systems, 2. analysis of herd composition and farmers' breeding practices and breed preferences and 3. impact assessment and key socio-economic determinants of the sustainability of tsetse and trypanosomosis control. This information forms the basis for analysis of policy options to enhance the income-earning capacity of crop-livestock farmers in the subhumid zone who are facing a growing demand for products of animal origin.